STUDY ON THE ROLE OF DRIVING SKILLS IN PHYSICAL EDUCATION LESSON AT PRIMARY RING (GYMNASIUM, 2017)
Physical education and sport know nowadays an unprecedented development. And effectively contributing directly to the formation and development of fair and multilateral personality, they exert remarkable influence in the direction of preserving and improving health, and spiritual potential of students biomotric tackling sedentary specific harmful influences. Between physical education and other educational branches (the intellectual, emotional, moral-volitional, aesthetics) there is a definite connection.The practicality of physical education, active presence of students during lessons, countless repetitions of exercises, solutions, behaviors, gestures, attitudes, etc. enable physical exercise influences the orientation towards the major goals of education. Physical education is used as a teaching aid in the formation and development of basic skills, skills, habits, skills and traits with broad-value in everyday activity of students. Knowing children's passion for movement, play and sports activities, our duty to capitalize channel influences exercise correctly so, with strengthening the body, the personality of the child to be positively influenced morally, emotionally and intellectually.